Isolation and Characterisation of a Lactococcal Plasmid and Preliminary Construction of a Lactococcus - E. Coli Shutile Vector - Rizlan Ross, Ernie Eileen (2001)
A total of 38 isolates from the ceaca1 content of two weeks old chicks were positively identified as Lactococcus lactis using API 50 CH Identification kit (bioMerieux, France). Plasmid analysis was performed on all 38 isolates. Seven isolates (A105, B61, B106, C5, C62, C119 and 041) were found to carry small sized plasmid Antibiogram of the seven isolates against seven antibiotics showed that all of them being susceptible to ampicillin (10 µg) and penicillin (10 µg). All isolates were found to be resistant to streptomycin (10 µg), gentamycin (10 µg) and kanamycin (30 µg). Only isolate B61 showed susceptibility towards erythromycin whereas the others showed resistance. An erythromycin resistant plasmid from isolate C5 was successfully electro-transformed into a plasmidless L. lactis MG 1363. The plasmid, designated pAJ01, was characterized by restriction endonuclease digestions. From the digestion results, a Lactococcus - E. coli shuttle vector was constructed by the ligation of plasmid pAJ0l with pUC19 at their EcoRI site. The recombinant plasmid designated pAJ02 was shown to be able to replicate well in both E. coli and Lactococcus. Both the plasmids pAJ0l and pAJ02 were found to be highly stable in Lactococcuv with the estimated stability of 100% and 98% respectively. The partial sequence of the plasmid pAJ01 was obtained and analysed for open reading frames (ORF). Two ORFs were identified and by using Basic Local Alignment Search Tools (BLAST) programme provided by National Center for Biotechnology Information (http://www.ncbi.nlm.nih.gov), the two ORFs were identified as replication gene and erythromycin resistance gene. Full sequences of the two genes were obtained.